An Analysis of English Pronunciation Difficulties and Influencing Factors Used by Sundanese Students - Astuti, Riyanti Sri; Widianingsih, Ayang Winda Sri; Kulsum, Eva Meidi (Communication In Research And Publications, 2025)
This study aims to investigate English pronunciation among Sundanese students in the English Education Department at Ma'soem University. Specifically, this study aims to analyze difficulties, identify factors, and explore strategies to overcome pronunciation difficulties often experienced by these students. Using a descriptive qualitative approach, this study collected data through classroom observations, questionnaires, and interviews involving 21 Sundanese students majoring English Eduction Department Fourth Semester in Ma’soem University. The results of the study indicate that pronunciation difficulties are generally divided into two levels: segmental and suprasegmental. Segmental issues include incorrect pronunciation of new or unfamiliar words, confusion between words that sound similar, difficulty in pronouncing vowel groups, and errors in diphthong pronunciation. Suprasegmental challenges include difficulty in aligning spelling with pronunciation, incorrect word stress, and inappropriate intonation patterns. Factors influencing these issues include strong interference from the mother language language , limited exposure to authentic English input, student-related variables such as motivation and confidence, and a tendency to pronounce English words based on their written form. To overcome these challenges, students employ several strategies, including phonetic training and increased phonological awareness, active listening and imitation of native speakers, receiving feedback and corrections from classmates or instructors, and utilizing technological tools such as pronunciation apps and online resources. The implications of this research highlight the importance of incorporating systematic pronunciation instruction into English language curricula, particularly for students from local language backgrounds. It also underscores the need for educators to provide more native-like input and corrective feedback to support pronunciation development among Sundanese learners.